2013
DOI: 10.1155/2013/526905
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural Study of Captive Sloth Bears Using Environmental Enrichment Tools

Abstract: Effects of environmental enrichment on behavioural changes were studied in five captive sloth bears kept in confined enclosure at Zoological Park, Chennai, India. Behavioural categories like active, passive, and abnormal behaviours were taken for the study. The activity budget was recorded as a single animal scan. The detailed baseline data of 150 hours, over a period of 30 days, were collected. At baseline, bears exhibited passive and more abnormal behaviours. Similarly, after application of the environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Behaviours like affiliation or aggression were rarely observed; this could be due to the fact that all the brown bears are female, thus having lower aggression displays [ 33 ]. As for affiliation, bears tend to be solitary animals, so low affiliation observations are expected [ 33 , 37 , 38 ]. A Montaudouin and Le Pape study [ 37 ] has shown that a large number of bears show stereotypic behaviour due to the small or unnatural enclosures or the absence of landmarks such as pools or ponds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Behaviours like affiliation or aggression were rarely observed; this could be due to the fact that all the brown bears are female, thus having lower aggression displays [ 33 ]. As for affiliation, bears tend to be solitary animals, so low affiliation observations are expected [ 33 , 37 , 38 ]. A Montaudouin and Le Pape study [ 37 ] has shown that a large number of bears show stereotypic behaviour due to the small or unnatural enclosures or the absence of landmarks such as pools or ponds.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, felids have more expressive behaviours: they use different body stances and vocalisations, as well as facial, ear, or tail movements, and positions to show their behaviour and feelings, such as vigilance, anger, fear, submission, and affiliation, at the time [ 54 , 55 ]. On the contrary, bears are not so expressive, and females have less affiliative behaviour since they are solitary species [ 33 , 37 , 38 ]. None of the animals in this study exhibited very low frequencies of affiliative, aggressive, and vocal behaviour ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sloth bear population in India has declined alarmingly due to habitat loss, poaching, the use of bear gall bladder in traditional medicine [33] and predation by tigers [6]. Infectious diseases such as leptospirosis and tuberculosis have also contributed to the decline of sloth bear population [38,39]. However, reporting of leptospirosis in sloth bears has been rare due to unavailability of penside diagnostics.…”
Section: Introductionmentioning
confidence: 99%
“…However, reporting of leptospirosis in sloth bears has been rare due to unavailability of penside diagnostics. In India, the only instance where leptospirosis was previously reported in sloth bear was in Nehru Zoological Park, Hyderabad [38].…”
Section: Introductionmentioning
confidence: 99%